2017
DOI: 10.1371/journal.pone.0177305
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-activated prodrug TH-302 decreased survival rate of canine lymphoma cells under hypoxic condition

Abstract: We tested the hypotheses that hypoxic stimulation enhances growth potentials of canine lymphoma cells by activating hypoxia-inducible factor 1α (HIF-1α), and that the hypoxia-activated prodrug (TH-302) inhibits growth potentials in the cells. We investigated how hypoxic culture affects the growth rate, chemoresistance, and invasiveness of canine lymphoma cells and doxorubicin (DOX)-resistant lymphoma cells, and influences of TH-302 on survival rate of the cells under hypoxic conditions. Our results demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…[6][7][8][9] A randomised phase II trial showed that adding TH-302 to gemcitabine therapy improved progression-free survival compared with gemcitabine alone in patients with untreated advanced-stage pancreatic cancer 7 We have previously reported that hypoxia enhances the growth potential of canine B-cell lymphoma cells by activating the HIF-1α signalling pathway; Evo decreased cellular survival rate under hypoxic conditions. 5 Our findings can contribute to the development of Evo-based hypoxia-targeting therapy for B-cell lymphoma in dogs.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…[6][7][8][9] A randomised phase II trial showed that adding TH-302 to gemcitabine therapy improved progression-free survival compared with gemcitabine alone in patients with untreated advanced-stage pancreatic cancer 7 We have previously reported that hypoxia enhances the growth potential of canine B-cell lymphoma cells by activating the HIF-1α signalling pathway; Evo decreased cellular survival rate under hypoxic conditions. 5 Our findings can contribute to the development of Evo-based hypoxia-targeting therapy for B-cell lymphoma in dogs.…”
mentioning
confidence: 78%
“…Hypoxic stimulation effectively improves growth potential and invasiveness of cancer cells in response to upregulation of the HIF-1α targeted genes. 2,5 One report suggested that HIF-1α may regulate expression levels of O( 6)-methylguanine-DNA methyltransferase (MGMT), which develop resistance to an alkylating agent, and HIF-1α knockdown can decrease MGMT expression. 20 Therefore, the HIF-1α signalling pathway may contribute to the malignant progression and chemoresistance of canine ITL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 TH-302 could suppress canine lymphoma survival by downregulating HIF-1α and its downstream genes. 41 Triggering Br-IPM release from TH-302 was accompanied by enhanced cytotoxicity when pO 2 was ,76 mmHg, according to electron paramagnetic resonance monitoring. 42 Nonpharmacological methods could exacerbate tumor hypoxia and therefore increase the in vitro and in vivo TH-302 cytotoxicity in pancreatic tumors.…”
Section: Nitroaromatics/nitroimidazolementioning
confidence: 96%
“…Evofosfamide (also known as TH302), a hypoxiaactivated prodrug, has shown the ability to selectively kill cells by DNA damage in hypoxic tissues and significantly reduce the volume of tumors, especially tumors with massive hypoxic regions. Furthermore, TH302 can spread into peripheral normoxic regions once activated, which is called the bystander effect [41][42][43][44][45].…”
Section: Open Accessmentioning
confidence: 99%